A multifunctional flexible sensor with coupling bionic microstructures inspired by nature. Issue 31 (14th July 2022) - Liu, Linpeng; Meng, Xiancun; Zhang, Changchao; Chen, You; Sun, Tao; Lu, Zhilai; Zhang, Junqiu; Niu, Shichao; Han, Zhiwu; Duan, Ji-An
Abstract : A strategy of coupling bionics is adopted on a paper-based sensor to achieve these excellent functions simultaneously, including multivariable detection, ultrasensitivity, waterproof and underwater applications. Abstract : For sensors, it is not difficult to achieve only one of the following critical functions: monitoring multimechanical signals, working in demanding environments, being environmentally friendly, being low cost, or showing high sensitivity or stability. However, it remains a major challenge, or even impossible, to simultaneously realize all these indicators in one sensor. Even in nature, some organisms are well known to have just one unique capacity, rather than entirely perfect features. Herein, inspired by arthropods' slit organs, microslit structures were introduced into the basic framework of sensors to realize strain and pressure detection. A second capability, waterproofness, was often achieved via coatings to form plant-inspired superhydrophobic surfaces. Meanwhile, paper, with the merits of being low cost and biodegradable, was selected to fabricate a paper-based sensor. This sensor is compatible with the high-sensitivity detection of multiple signals and can be used in extreme underwater environments. It is also low cost and degradable, inspired by, but far advanced beyond, natural creatures. Finally, this sensor has strain sensitivity of 100, pressure sensitivity of 0.43% kPa −1, a strain resolution of 0.003%, and a pressure sensing range exceeding 160 kPa. Meanwhile, it exhibits superhydrophobicity, with a water contact angle of up to 152.3° and a sliding angle of 7.3°. It is demonstrated that this sensor can be applied to monitor human joint or muscle motion in wearable electronics. It can also be used for various tactile sensing applications in certain environments under humid or aqueous conditions.